The meanings of adduction and delaying in directing the synatactic judementin in Al Khateeb Al Sharbenys explanation. (Journal of Hama University, 2025)
This research aims to study the relation between adduction, delaying and syntax in Al khteeb Al Sharbenys explanation : Al Serage Al Moneer in Understanding the Meaning of Words of Allah Al Hakeem Al khabeer . It is asyntactic and rhetorical study which gives the target .The research begins with the definition of the syntax , adduction and delaying in linguistic and idamatic way , then reffering to the meanigs which explain the syntax of the adduction which should be delayed and the opposite is right .Al Sharbeny has aimed in his explanation to employ the syntax to clarify the meaning which facilitates the reads to understand the verses in a scientific style . AlSharbeny was one of the grammarairs who has aimed to explain the Quran and the verses by connecting between syntax and semantics I clarify all these points in my study which explains the connection between adduction , delaying and syntax in Al Quran verses .